Selective deficiencies in descending inhibitory modulation in neuropathic rats: implications for enhancing noradrenergic tone. Issue 9 (September 2018) - Patel, Ryan; Qu, Chaoling; Xie, Jennifer Y.; Porreca, Frank; Dickenson, Anthony H.
Abstract : Abstract: Pontine noradrenergic neurones form part of a descending inhibitory system that influences spinal nociceptive processing. Weak or absent descending inhibition is a common feature of chronic pain patients. We examined the extent to which the descending noradrenergic system is tonically active, how control of spinal neuronal excitability is integrated into thalamic relays within sensory-discriminative projection pathways, and how this inhibitory control is altered after nerve injury. In vivo electrophysiology was performed in anaesthetised spinal nerve–ligated (SNL) and sham-operated rats to record from wide dynamic range neurones in the ventral posterolateral thalamus (VPL). In sham rats, spinal block of α2 -adrenoceptors with atipamezole resulted in enhanced stimulus-evoked and spontaneous firing in the VPL, and produced conditioned place avoidance. However, in SNL rats, these conditioned avoidance behaviours were absent. Furthermore, inhibitory control of evoked neuronal responses was lost, but spinal atipamezole markedly increased spontaneous firing. Augmenting spinal noradrenergic tone in neuropathic rats with reboxetine, a selective noradrenergic reuptake inhibitor, modestly reinstated inhibitory control of evoked responses in the VPL but had no effect on spontaneous firing. By contrast, clonidine, an α2 agonist, inhibited both evoked and spontaneous firing, and exhibited increased potency in SNL rats compared with sham controls. These data suggest descending noradrenergic inhibitory pathways are tonically active in sham rats. Moreover, in neuropathic states, descending inhibitory control is diminished, but not completely absent, and distinguishes between spontaneous and evoked neuronal activity. These observations may have implications for how analgesics targeting the noradrenergic system provide relief. Abstract : Supplemental Digital Content is Available in the Text.Descending noradrenergic pathways modulate spontaneous but not evoked thalamic neuronal hyperexcitability in neuropathic pain states. Spinal clonidine inhibits evoked and spontaneous firing, whereas reboxetine selectively inhibits evoked firing.